PERANCANGAN SISTEM INFORMASI AKUNTANSI LAPORAN KEUANGAN (STUDI KASUS PADA YPM SALMAN ITB) - Rio Yunanto; M Munayah; Ony Widilestariningtyas (Labkat Press KA FTIK UNIKOM, 2012)
Yayasan Pembina masjid (YPM) Salman ITB is the foundation that manages the activities of religious service. The process of recording transactions in both of revenue and expenditure on the ledgers are still using Microsoft Office Excel as a tool for data processing. Financial statements prepared by the YPM Salman ITB is not fully using the islamic principles. For these problem the writer take the title